All-fiber probing of aluminized RDX particle micro-explosion - Zhang, Yu; Su, Wenjie; Qin, Yifan; Jin, Wei; Zhang, Yaxun; Liu, Zhihai; Yuan, Libo (Frontiers in Physics, 2023)
Investigating the thermal decomposition characteristics and mechanisms of nano- and submicron-aluminized 1,3,5-trinitro-1,3,5-triazine (RDX) is essential to optimize the formulations and improve combustion/detonation efficiencies. However, no research has focused on the microscopic scale of a single aluminized RDX particle. We demonstrate an all-fiber probing method for the violent thermal decomposition of a single nano-aluminized micron-RDX particle, which we address as micro-explosion in this paper. We believe studying micro-explosion will be beneficial to the research of thermal decomposition. In experiments, we first characterize the micro-explosion as a three-step process, i.e., melting, first decomposition, and second decomposition. Then, we measure micro-explosion properties, i.e., shockwave-like flow velocity, initiation energy threshold, and shockwave-like flow pressure. Among the aluminized RDX particles with 0%, 5%, 10%, 15%, 20%, 25%, and 30% surface coverage ratios (SCRs), the sample with 20% SCR shows the highest flow velocity and force, which are about 69.9 mm/s and 39.4 μN, respectively. Moreover, the threshold decreases with rising SCRs, and the mean threshold of 30% SCR is 75 μJ. The experimental results prove that the all-fiber micro-explosion probing method is feasible, safe, and robust.